(untitled) - Reischauer, Edwin O. (Sydney, 1989)
One of two texts which introduce East Asian history, both have been rewritten to take account of the changes in China since Mao's death, of Japan's economic success, and of the emergence of Taiwan, South Korea and Singapore as important political and economic powers. They aim to combine authoritative scholarship with comprehensive coverage and a succinct, readable style and are aimed at undergraduate students and the general reader. Japan is a land of modest geographic size, but it is one of the larger countries of the world by population and today is the world's economic powerhouse. Though in culture it is a daughter of ancient China, Japan has developed one of the most distinctive cultures in the world.
Keywords: Japan; History